Single‐stage laparoscopic cholecystectomy and intraoperative endoscopic retrograde cholangiopancreatography: is this strategy feasible in Australia?. Issue 11 (21st July 2016) - March, Brayden; Burnett, David; Gani, Jon
Abstract : Currently in Australasia, concomitant cholecystolithiasis and choledocholithiasis are usually managed with two procedures: laparoscopic cholecystectomy (LC) and pre or postoperative endoscopic retrograde cholangiopancreatography (ERCP). This approach exposes the patient to the risk of complications from the common bile duct stone(s) while awaiting ERCP, the risks of the ERCP itself (particularly pancreatitis) and the need for a second anaesthetic. This article explores the evidence for a newer hybrid approach, single stage LC and intraoperative ERCP (SSLCE) and compares this approach with the commonly used alternatives. SSLCE offers reduced rates of pancreatitis, reduced length of hospital stay and reduced cost compared with the two‐stage approach and requires only one anaesthetic. There is a reduced risk of bile leak compared with procedures that involve a choledochotomy, and ductal clearance rates are superior to trans‐cystic exploration and equivalent to the standard two‐stage approach. Barriers to widespread implementation relate largely to operating theatre logistics and availability of appropriate endoscopic expertise, although when bile duct stones are anticipated these issues are manageable. There is compelling justification in the literature to gather prospective evidence surrounding SSLCE in the Australian Healthcare system.